2007
DOI: 10.1063/1.2742599
|View full text |Cite
|
Sign up to set email alerts
|

Powerful polymeric thermal microactuator with embedded silicon microstructure

Abstract: A powerful and effective design of a polymeric thermal microactuator is presented. The design has SU-8 epoxy layers filled and bonded in a meandering silicon ͑Si͒ microstructure. The silicon microstructure reinforces the SU-8 layers by lateral restraint. It also improves the transverse thermal expansion coefficient and heat transfer for the bonded SU-8 layers. A theoretical model shows that the proposed SU-8/Si composite can deliver an actuation stress of 1.30 MPa/ K, which is approximately 2.7 times higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…doi:10.1016/j.ijsolstr.2008.05.016 insulator. Experimental testing of a micro-machined device confirmed that the polymeric actuator with the embedded skeleton exhibits excellent actuation capability (Lau et al, 2006a(Lau et al, , 2007b.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…doi:10.1016/j.ijsolstr.2008.05.016 insulator. Experimental testing of a micro-machined device confirmed that the polymeric actuator with the embedded skeleton exhibits excellent actuation capability (Lau et al, 2006a(Lau et al, , 2007b.…”
Section: Introductionmentioning
confidence: 57%
“…Such integration exploits the large thermal expansion and stiffness mismatches between the two materials to enhance the actuation performance of the polymer. This leads to a new class of powerful thermal micro-actuators (Lau et al, 2006a(Lau et al, , 2007b.…”
Section: Introductionmentioning
confidence: 99%
“…The confinement of the polymer material causes a concentration of the thermal strains in the in-plane direction thus enhancing the total actuator displacement [7].…”
Section: Micro Gripper Design and Fabricationmentioning
confidence: 99%
“…The actuator is 85 µm wide and 30 µm thick. These dimensions have been chosen according to the analysis presented in [7] such that there is an effective confinement of the polymer material and a large transverse heat conduction coefficient, thus improving heat spreading across the insulating polymer. An integrated aluminium heater is defined on the top of the silicon structure.…”
Section: Micro Gripper Design and Fabricationmentioning
confidence: 99%
“…Moreover, the thermal expansion of this actuator is enhanced due to the constraint effect of polymer layers between rigid silicon plates. 3 A calculation of compressed displacement of a constrained rubber between two rigid surfaces based on the hydrostatic pressure is reported in Ref. 4.…”
mentioning
confidence: 99%